TELAAH KRITIS ILMU KEPEMIMPINAN PERSPEKTIF KONSEP PARTIKEL DASAR PENYUSUN ATOM UNTUK MEMBENTUK KARAKTER PEMIMPIN HARAPAN - Mustofa (Discovery, 2020)
Abstract: The education sector or school for the Indonesian nation is a strategic industry of civilization to form a generation with character in the future. Nowadays, it has very tough challenges in the form of a character crisis, human resources and a leadership crisis. The urgent problem that will be described in the discussion of this article is how leadership science at the atomic level is the perspective of learning the basic atomic particles, what is the importance of the results of the analysis of leadership science at the atomic level for the development of character education in schools and how efforts should be made to make the education sector or schools as factories for Indonesian human civilization in the future. The science of leadership at the atomic level that can be developed in the study of the basic particles that make up atoms requires, among others, that the leader has competence, integrity, wisdom and commitment. The results of the analysis of leadership science at the atomic level in the perspective of learning the basic particles of atomic constituents are very important to provide meaningful experience about the character of storage in the future. Efforts that must be made to make the education sector or schools as factories for Indonesian human trafficking in the future are to encourage awareness from all parties to work together in a real, honest and oriented manner towards enhancing the character and development of superior Indonesian human resources. Keywords: leadership, elementary particles of atoms, character. Abstrak: Sektor pendidikan atau sekolah bagi bangsa Indonesia adalah industri strategis peradaban untuk membentuk generasi berkarakter di masa depan saat ini memiliki tantangan yang sangat berat berupa krisis karakter, SDM dan krisis kepemimpinan. Masalah urgen yang akan diuraikan pada pembahasan artikel ini adalah bagaimana ilmu kepemimpinan pada level atomik perspektif pembelajaran patikel dasar penyusun atom, apa pentingnya hasil analisis tentang ilmu kepemimpinan pada level atomik bagi pengembangan pendidikan karakter di sekolah dan bagaimana usaha yang harus dilakukan untuk menjadikan sektor pendidikan atau sekolah sebagai pabrik-pabrik peradapan manusia Indonesia di masa yang akan datang. Ilmu kepemimpinan pada level atomik yang dapat dikembangkan dalam pembelajaran partikel dasar penyusun atom antara lain mensyaratkan agar pemimpin itu memiliki kompetensi, integritas, bijaksana dan komitmen. Hasil analisis tentang ilmu kepemimpinan pada level atomik perspektif pembelajaran patikel dasar penyusun atom sangat penting untuk memberi pengalamam bermakna tentang karakter pemimpan di masa yang akan datang. Usaha yang harus dilakukan untuk menjadikan sektor pendidikan atau sekolah sebagai pabrik-pabrik peradapan manusia Indonesia di masa yang akan datang adalah mendorong kesadaran dari semua pihak untuk bersama-sama bekerja secara nyata, jujur dan berorientasi pada peningkatan karakter dan pengembangan sumber daya manusia Indonesia yang unggul. Kata kunci: kepemimpinan, partikel dasar penyusun atom, karakter.